High peri-coronary inflammation assessed by coronary CT angiography predicts cardiovascular events in type 2 diabetes mellitus patients. (14th October 2021) - Ichikawa, K; Miyoshi, T; Miki, T; Nakamura, K; Ito, H
Abstract: Background: Type 2 diabetes mellitus (T2DM) is associated with an increased risk of cardiovascular (CV) events, therefore there is a need to identify T2DM patients at higher risk. A novel imaging biomarker, the peri-coronary adipose tissue (PCAT) attenuation on coronary CT angiography (CTA), reflects peri-coronary inflammation. We hypothesized that the assessment of PCAT attenuation is useful for risk stratification in T2DM patients. Purpose: We aimed to investigate whether high PCAT attenuation is related to increased risk of CV events in T2DM patients. Methods: This study is a post-hoc analysis of the prospective cohort study consist of T2DM patients who underwent clinically indicated coronary CTA at a Japanese University Hospital. As CT findings, coronary artery calcium score, epicardial adipose tissue volume, high-risk plaque features (positive remodeling, low density plaque, spotty calcification), significant stenosis (>50% luminal narrowing), and PCAT attenuation were examined. PCAT attenuation was assessed in Hounsfield units (HU) of proximal 40-mm segments of the left anterior descending artery. CV events was defined as CV death, acute coronary syndrome, and hospitalization for heart failure. Results: In a total of 333 T2DM patients (63% male, age 66±11 years), the mean PCAT attenuation was −70.6±6.1 HU. During the follow-up period of 4.2 years, 20 CV events (2 cases of CV death, 14 of acute coronary syndrome, 4 of heart failure) were confirmed. Patients with CV events had higher PCAT attenuation than those without CV events (−67.4 vs −70.8 HU, p=0.013). Multivariate linear regression analysis revealed that the independent determinants of PCAT attenuation were male (p<0.001) and statin use (p=0.024). In univariate Cox regression analyses, high-risk plaque features (HR 4.837, 95% CI 1.120–20.895, p=0.035), significant stenosis (HR 2.852, 95% CI 1.159–7.015, p=0.022), and PCAT attenuation (HR 1.119, 95% CI 1.34–1.212, p=0.005) were significantly associated with CV events. On the other hand, coronary artery calcium score (p=0.055) and epicardial adipose tissue volume (p=0.449) were not significantly associated with CV events. In multivariate Cox regression analysis, PCAT attenuation was independently associated with CV events after adjustment for coronary CTA findings and traditional CV risk factors (HR 1.105, 95% CI 1.017–1.200, p=0.018). Receiver operating characteristic curve analysis showed the optimal cut-off value of PCAT attenuation to predict CV events was −69.3 HU (sensitivity 58.5%, specificity 65.0%). Kaplan-Meier analysis showed that patients with high PCAT attenuation (≥−69.3 HU) had more CV events than those with low PCAT attenuation (p=0.013, log-rank test). Conclusion: High PCAT attenuation was a strong predictor of CV events in T2DM patients independent of coronary CTA findings and traditional risk factors. Our study suggested that assessment of PCAT attenuation could be a valuable tool for risk stratification in T2DM patients. Funding Acknowledgement: Type of funding sources: None.